Pola Alokasi Buruh Tani dan Pengaruhnya Terhadap Produktivitas Usahatani Melon: Pendekatan Generalized Additive Model - Evi Irawan; Agustono Agustono; Isnarosan Suci Andriani (JSEP (Journal of Social and Agricultural Economics), 2023)
Even though it is known that melon farming is labor-demanding, the allocation of hired labor is often overlooked as the subject of melon farming studies. To fill this void, this study aims to analyze the pattern of farm labor allocation and its effect on the productivity of melon farming. The data used in this research is primary data collected through a survey of 60 melon farmers selected using the convenience sampling method by considering the area of farming land. Data analysis included descriptive statistical analysis and non-parametric regression, namely the generalized additive model. The research results show that: (1) labor costs account for nearly 50% of variable production costs; (2) melon farms with a land area of more than 0.5 ha tend to employ more farm laborers than farms with less than 0.5 ha. Farm workers are even employed for farming activities that fall into the category of delicate works and have a significant impact on production, such as pest and disease control, pruning shoots, and fruit selection; and (3) the use of farm laborers in delicate works farming activities reduces melon productivity.